Anti-aging heat-conducting polyurethane adhesive and preparation method thereof

By using nano-alumina copper in aqueous polyurethane adhesive and loading β-alanine methyl ester hydrochloride and parabenzamide, and introducing 4-toluene hydroamine resin, the shortcomings of existing aqueous polyurethane adhesives in aging resistance and thermal conductivity are solved, and high-performance and low-cost adhesive preparation are achieved.

CN119614135AInactive Publication Date: 2025-03-14GUANGZHOU FUSIDA CHEM PROD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510153459.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing water-based polyurethane adhesives have shortcomings in aging resistance and thermal conductivity, and the large amount of addition of functional fillers will lead to uneven performance and increased cost.

Method used

By using nano-alumina copper as a functional raw material and loading β-alanine methyl ester hydrochloride and para-hydroxybenzamide on its surface, an organic layer with a variety of polar groups such as amino groups is formed, thereby improving the dispersion and stability of nano-alumina copper in aqueous polyurethane emulsion. At the same time, 4-toluene hydroamine resin is introduced to enhance the structural stability and aging resistance of the adhesive.

Benefits of technology

It achieves excellent aging resistance and thermal conductivity without the need for large amounts of high-performance fillers, reducing costs and improving the overall performance and environmental friendliness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides an anti-aging heat-conducting polyurethane adhesive and a preparation method thereof, and belongs to the technical field of adhesives, and the preparation method comprises the following steps: homogenizing pretreated nano aluminum oxide copper and silane in water, then adding beta-alanine methyl ester hydrochloride and p-hydroxybenzamide, homogenizing to obtain a suspension, and drying to obtain the anti-aging heat-conducting polyurethane adhesive. Sequentially adding polyacrylic acid and the suspension into water, heating, stirring, cooling, centrifuging and drying to obtain modified nano aluminum oxide copper, and then adding the modified nano aluminum oxide copper into a waterborne polyurethane emulsion for stirring to obtain a mixed emulsion; ethyl p-hydroxyphenylacetate is added into 4-toluene hydroamine resin and water for homogenization, then the mixed emulsion is added for heating and stirring, and modified emulsion is obtained; and pouring the modified emulsion into a mold, and curing to obtain the anti-aging heat-conducting polyurethane adhesive. According to the technical scheme provided by the invention, excellent aging resistance and heat-conducting property can be realized without adding a large amount of high-performance filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to an aging-resistant heat-conductive polyurethane adhesive and a preparation method thereof. Background Art

[0002] Adhesives have always played an important role in human life and are often used in home furnishing, decoration, medical treatment, shipbuilding, aerospace, equipment, electronic devices and other fields. At present, waterborne polyurethane adhesives that are environmentally friendly and have excellent comprehensive performance are increasingly valued by people, but the bonding strength of polyurethane used in the preparation of waterborne polyurethane adhesives is poor, and the adhesion to the substrate is poor, which cannot meet the increasingly high production requirements of adhesives. At the same time, with the expansion of application fields such as electronics, automobiles and aerospace, the process adaptability of waterborne polyurethane adhesives in different application scenarios also needs to be further optimized, such as meeting specific requirements such as aging resistance and thermal conductivity to ensure effective heat transfer of high-power devices and extend service life. In the process of preparing waterborne polyurethane adhesives with excellent performance, in order to improve the performance of the product, it is usually necessary to add a large amount of functional fillers, and the addition amount is generally 30%~70%. However, the large amount of such functional fillers can easily cause uneven dispersion inside the adhesive, resulting in large differences in the overall performance of the adhesive, affecting the quality of the final product. In addition, high-performance functional fillers and additives are often expensive, and the large-scale use of these materials will also significantly increase the cost of adhesives.

[0003] The patent application document with publication number CN117866579A discloses a polyurethane adhesive for energy storage batteries and a preparation method thereof, which is composed of components A and B; the raw materials of component A include, by weight: 20 to 25 parts of oil polyol, 5 to 10 parts of silane-modified polyol, 1 to 2 parts of chain extender, 1 to 5 parts of molecular sieve, 60 to 70 parts of surface-modified thermally conductive filler, and 0.2 to 0.5 parts of adhesion promoter; the raw materials of component B include, by weight: 30 to 40 parts of isocyanate prepolymer and 60 to 70 parts of surface-modified thermally conductive filler.

[0004] Although the polyurethane adhesive prepared in this patent application document has better weather resistance and higher bonding strength than traditional two-component polyurethane thermal conductive structural adhesives, the amount of thermal conductive filler added during the preparation of this patent application document is too large, far exceeding other components, which will not only increase the cost of the adhesive, but also cause a large difference in the overall performance of the adhesive, thereby affecting the quality of the product. In addition, the polyurethane used in the adhesive of this patent application document is not a finished raw material, but is prepared from polyols and isocyanate prepolymers, which is prone to produce more by-products during the preparation process, which will not only affect the performance of other components, but also have an impact on the environment.

[0005] Therefore, it is necessary to provide an aging-resistant thermally conductive polyurethane adhesive and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0006] In view of this, the present invention provides an aging-resistant heat-conductive polyurethane adhesive and a preparation method thereof, so as to improve the aging-resistant and heat-conductive properties of the polyurethane adhesive.

[0007] To achieve the above object, the present invention provides a method for preparing an aging-resistant thermally conductive polyurethane adhesive, comprising the following steps: S1. After homogenizing the pretreated nano-alumina copper and silane in water, add β-alanine methyl ester hydrochloride and p-hydroxybenzamide to homogenize to obtain a suspension; add polyacrylic acid and the suspension to water in sequence, heat and stir, cool, centrifuge and dry to obtain a modified nano-alumina copper, and then add the mixture to an aqueous polyurethane emulsion and stir to obtain a mixed emulsion; S2, adding ethyl p-hydroxyphenylacetate to 4-toluene hydrogenamine resin and water to homogenize, and then adding the mixed emulsion to heat and stir to obtain a modified emulsion; S3, pouring the modified latex into a mold for curing to obtain an aging-resistant thermally conductive polyurethane adhesive.

[0008] The present invention uses nano-aluminum oxide copper with certain thermal conductivity as a functional raw material, and forms an organic layer with multiple polar groups such as amino groups on the surface of nano-aluminum oxide copper by impregnation and loading β-alanine methyl ester hydrochloride and p-hydroxybenzamide under the coupling action of silane. Among them, β-alanine methyl ester hydrochloride is acidic in water, and can protonate the amino group, and form coordination and electrostatic interaction with the partially ionized hydroxyl and amide groups of p-hydroxybenzamide in water, and these interactions and acidic environment will also activate the phenolic hydroxyl group of p-hydroxybenzamide, so as to react with the free radicals generated by aging in the material, reduce the chain reaction of oxidative degradation and accelerated aging caused by free radicals, and thus improve the aging resistance of the material.

[0009] Subsequently, the polyacrylic acid and other groups are compounded through hydrogen bonding, and the good compatibility between polyacrylic acid and aqueous polyurethane emulsion is used to improve the dispersibility and stability of nano-aluminum oxide copper in aqueous polyurethane emulsion, and reduce the agglomeration phenomenon. At the same time, the methyl ester group of β-alanine methyl ester hydrochloride and the benzene ring structure of p-hydroxybenzamide form a more compact organic protective layer through hydrophobic interaction, blocking water penetration, reducing the influence of external environmental conditions, thereby reducing the aging rate of the material and improving the aging resistance of the material. This organic composite layer can also improve the dispersibility of nano-aluminum oxide copper, a thermal conductive material, in the matrix through good compatibility with aqueous polyurethane emulsion, forming a continuous thermal conductive path, improving the utilization rate of nano-aluminum oxide copper, and thus improving the thermal conductivity of the material.

[0010] The present invention introduces 4-toluene hydroamine resin in the preparation process of the modified emulsion, and forms a coordination effect with the amino group of the microporous structure on the surface of the resin and the hydroxyl group of ethyl p-hydroxyphenylacetate, so that the ethyl p-hydroxyphenylacetate is embedded in the microporous structure, which not only increases the number of phenolic hydroxyl groups, but also can interact with the activated phenolic hydroxyl groups in the modified nano-alumina copper composite, so that the structure after cross-linking is more stable, and the influence of oxidation or thermal degradation is reduced, thereby improving the aging resistance of the material. Subsequently, the structural stability of the adhesive is enhanced through cross-linking with the mixed emulsion, and the cracking or deformation of the material during the aging process is reduced, thereby enhancing the aging resistance of the material.

[0011] Optionally, in step S1, the nano-alumina copper complex is ultrasonically treated in ethanol at 500-600 r / min for 10-15 min, and then dried at 70-80° C. for 3-4 h to obtain the pretreated nano-alumina copper complex.

[0012] Optionally, in step S1, the suspension is obtained by homogenizing the pretreated nano-alumina copper complex and the silane coupling agent in water, and then adding β-alanine methyl ester hydrochloride and p-hydroxybenzamide for homogenization.

[0013] Optionally, in step S1, the homogenization speed is 600-800 r / min, and the homogenization time is 20-30 min; the silane coupling agent is any one of 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 3-(methacryloyloxy)propyltrimethoxysilane.

[0014] Optionally, in step S1, polyacrylic acid is added to water and mixed evenly, and then the suspension is added dropwise at a rate of 2 mL / min, and stirring is continued for 1 to 2 hours after the addition is completed. After cooling to room temperature, the mixture is centrifuged at 7000 to 8000 rpm for 5 to 10 minutes, and the precipitate is centrifuged with ethanol and water at 7000 to 8000 rpm for 5 to 10 minutes, respectively. The precipitate is vacuum dried at 70 to 80° C. for 6 to 10 hours to obtain modified nano-alumina copper, which is then added to an aqueous polyurethane emulsion and stirred to obtain a mixed emulsion.

[0015] The invention removes pollutants on the surface of nano-aluminum oxide copper by ultrasonic cleaning to obtain clean pretreated nano-aluminum oxide copper, and then increases the contact frequency between the nano-aluminum oxide copper and beta-alanine methyl ester hydrochloride and p-hydroxybenzamide under homogenization, and simultaneously adds a silane coupling agent to further enhance the physical adsorption between the nano-aluminum oxide copper and the beta-alanine methyl ester hydrochloride and p-hydroxybenzamide.

[0016] Optionally, in step S1, the mixed emulsion is obtained by stirring the modified nano-alumina copper in an aqueous polyurethane emulsion at 600-800 r / min for 1-2 hours.

[0017] Optionally, in step S2, the dispersant, mono- and di-glycerol fatty acid esters and 4-toluene hydrogenamine resin are added to water for homogenization, then ethyl p-hydroxyphenylacetate and vinyl MQ silicone resin are added for homogenization, then the dispersant and sodium dodecyl sulfate are added for homogenization, and finally the mixed emulsion is added for heating and stirring to obtain a modified emulsion.

[0018] The long-chain aliphatic structure of 4-toluene hydrogenamine resin and ethyl p-hydroxyphenylacetate added in the process of preparing the modified emulsion can interact with Si-O bonds in the vinyl MQ silicone resin through interactions between flexible and rigid structures and hydrogen bonds between polar groups, thereby increasing a certain physical crosslinking effect, thereby enhancing the interaction between molecules, and the enhanced interaction helps to reduce the degree of freedom of the chain segments, thereby increasing the bonding performance of the system. At the same time, this enhanced interaction also promotes the formation of a denser network structure, helps to reduce the damage to the material by external environmental conditions such as moisture, and further improves the aging resistance of the system.

[0019] Optionally, in step S2, the homogenization speed is 600~800r / min, and the homogenization time is 20~30min; the dispersant is 5040 dispersant; the heating and stirring temperature is 60~80℃, the speed is 500~600r / min, and the time is 6~8h.

[0020] During the preparation of the modified emulsion of the present invention, when blended with the mixed emulsion, the formation of hydrogen bonds between polar groups, the emulsification and dispersion effects of the 5040 dispersant, mono- and di-glycerol fatty acid esters, and sodium dodecyl sulfate can further enhance the binding force between the components, reduce interface defects, and help form a stable emulsion system.

[0021] Optionally, in step S3, the modified latex is poured into a mold, the mold surface is flattened with a scraper, pre-cured at 25-35° C. for 4-5 hours, and then cured at 70-80° C. for 12-15 hours to obtain an aging-resistant thermally conductive polyurethane adhesive.

[0022] In order to achieve the above-mentioned purpose, the present invention also provides an aging-resistant thermally conductive polyurethane adhesive, comprising the following raw materials in parts by weight: 10 parts of nano-alumina copper complex, 1 to 3 parts of β-alanine methyl ester hydrochloride, 1 to 2 parts of p-hydroxybenzamide, 2.5 to 5 parts of polyacrylic acid, 100 parts of aqueous polyurethane emulsion, 0.2 to 0.3 parts of 5040 dispersant, 0.1 to 0.2 parts of mono- and di-glycerol fatty acid esters, 1 to 2 parts of ethyl p-hydroxyphenylacetate, 4 to 7 parts of 4-toluene hydrogenamine resin, 3 to 4 parts of vinyl MQ silicone resin, and 0.1 to 0.2 parts of sodium dodecyl sulfate.

[0023] The technical solution provided by the present invention can achieve excellent aging resistance and thermal conductivity without adding a large amount of high-performance fillers, and also has certain environmental friendliness.

[0024] The above technical solution of the present invention includes at least the following beneficial effects: 1. In the present invention, nano-aluminum-copper is used as a functional raw material, and β-alanine methyl ester hydrochloride and p-hydroxybenzamide are loaded on its surface through impregnation and under the coupling effect of silane, forming an organic layer with multiple polar groups such as amino groups, which can be compounded with the long chain structure in polyacrylic acid through hydrophobic interaction, and the compatibility between polyacrylic acid and aqueous polyurethane emulsion is utilized to improve the dispersibility and stability of nano-aluminum-copper in aqueous polyurethane emulsion. At the same time, the formation of this organic composite layer also helps to reduce the agglomeration phenomenon, improve the utilization rate of nano-aluminum-copper, and thus improve the overall thermal conductivity of the material.

[0025] 2. In the process of preparing the modified nano-alumina copper complex of the present invention, the β-alanine methyl ester hydrochloride used is acidic in water and can protonate the amino group, forming coordination and electrostatic interactions with the partially ionized hydroxyl and amide groups of p-hydroxybenzamide in water, and these interactions and the acidic environment will also activate the phenolic hydroxyl groups of p-hydroxybenzamide, thereby reacting with the free radicals generated in the material due to aging, reducing the oxidative degradation caused by the free radicals and accelerating the chain reaction of aging, thereby improving the aging resistance of the material.

[0026] 3. In the preparation process of the modified emulsion of the present invention, the amino groups on the surface microporous structure of the added 4-toluene hydrogenamine resin can form a coordination effect with the hydroxyl group of ethyl p-hydroxyphenylacetate, increase the number of phenolic hydroxyl groups, and work together with the activated phenolic hydroxyl groups in the modified nano-alumina copper to make the structure more stable after cross-linking, reduce the influence of oxidation or thermal degradation, and further improve the aging resistance of the material. Subsequently, the structural stability of the adhesive is enhanced through cross-linking with the mixed emulsion, and the cracking or deformation of the material during the aging process is reduced, thereby enhancing the aging resistance of the material.

[0027] 4. The preparation process of the present invention is streamlined, no by-products are generated, and the equipment used is low in cost, which has certain environmental friendliness and cost advantages. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0029] The nano-alumina copper complex used in the following examples was purchased from Alfa Aesar (China) Chemical Co., Ltd.; β-alanine methyl ester hydrochloride was purchased from Shanghai McLean Biochemical Co., Ltd.; and dispersant 5040 was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.

[0030] Example 1 10 parts of nano-alumina copper were added to 100 parts of anhydrous ethanol, ultrasonicated at 500r / min for 10 minutes, and then dried at 70°C for 4 hours to obtain pretreated nano-alumina copper. 5 parts of pretreated nano-alumina copper and 0.1 parts of 3-aminopropyltriethoxysilane were added to 50 parts of deionized water, homogenized at 800r / min for 20 minutes, and then 1 part of β-alanine methyl ester hydrochloride and 2 parts of p-hydroxybenzamide were added, and homogenized at 700r / min for 20 minutes to obtain a suspension. 5 parts of polyacrylic acid were added to 50 parts of deionized water and mixed evenly, and then the suspension was added dropwise at a speed of 2mL / min. After the addition was completed, stirring was continued for 2 hours. After cooling to room temperature, it was centrifuged at 8000rpm for 5 minutes, and the precipitate was centrifuged at 8000rpm for 5 minutes with anhydrous ethanol and deionized water, and the precipitate was vacuum dried at 80°C for 8 hours to obtain modified nano-alumina copper. 10 parts of modified nano-alumina copper were added into 100 parts of aqueous polyurethane emulsion, and stirred at 800 r / min for 2 hours to obtain a mixed emulsion.

[0031] Add 0.1 part of 5040 dispersant, 0.2 part of mono- and di-glycerol fatty acid esters and 5 parts of 4-toluene hydrogenamine resin to 50 parts of deionized water, homogenize at 800r / min for 30min, then add 1 part of ethyl p-hydroxyphenylacetate and 4 parts of vinyl MQ silicone resin, homogenize at 700r / min for 30min, then add 0.1 part of 5040 dispersant and 0.1 part of sodium dodecyl sulfate, homogenize at 600r / min for 30min, finally add the mixed emulsion, stir at 500r / min for 6h at 80℃ to obtain the modified emulsion. Take 5 parts of the modified emulsion and pour it into a mold with a size of 10×20mm and a thickness of 3mm, scrape the surface of the mold flat with a scraper, pre-cure at 30℃ for 5h, then cure at 80℃ for 12h, take it out after cooling, and obtain the aging-resistant thermal conductive polyurethane adhesive.

[0032] Example 2 10 parts of nano-alumina copper were added to 100 parts of anhydrous ethanol, ultrasonicated at 600r / min for 10min, and then dried at 70°C for 3h to obtain pretreated nano-alumina copper. 6 parts of pretreated nano-alumina copper and 0.1 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane were added to 50 parts of deionized water, homogenized at 600r / min for 20min, and then 2 parts of β-alanine methyl ester hydrochloride and 1 part of p-hydroxybenzamide were added, and homogenized at 600r / min for 30min to obtain a suspension. 4 parts of polyacrylic acid were added to 50 parts of deionized water and mixed evenly, and then the suspension was added dropwise at a speed of 2mL / min. After the addition was completed, stirring was continued for 2h, and after cooling to room temperature, it was centrifuged at 8000rpm for 8min, and the precipitate was centrifuged at 8000rpm for 10min with anhydrous ethanol and deionized water, and the precipitate was vacuum dried at 70°C for 6h to obtain modified nano-alumina copper. 9 parts of modified nano-alumina copper were added into 100 parts of aqueous polyurethane emulsion, and stirred at 800 r / min for 1.5 hours to obtain a mixed emulsion.

[0033] Add 0.1 part of 5040 dispersant, 0.15 parts of mono- and di-glycerol fatty acid esters and 6 parts of 4-toluene hydrogenamine resin to 50 parts of deionized water, homogenize at 700r / min for 30min, then add 2 parts of ethyl p-hydroxyphenylacetate and 3 parts of vinyl MQ silicone resin, homogenize at 600r / min for 30min, then add 0.1 part of 5040 dispersant and 0.15 parts of sodium dodecyl sulfate, homogenize at 600r / min for 30min, finally add the mixed emulsion, stir at 500r / min for 7h at 70℃ to obtain the modified emulsion. Take 5 parts of the modified emulsion and pour it into a mold with a size of 10×20mm and a thickness of 3mm, scrape the surface of the mold flat with a scraper, pre-cure at 30℃ for 4.5h, then cure at 75℃ for 14h, take it out after cooling, and obtain the aging-resistant thermal conductive polyurethane adhesive.

[0034] Example 3 10 parts of nano-alumina copper were added to 100 parts of anhydrous ethanol, ultrasonicated at 600r / min for 15min, and then dried at 80°C for 4h to obtain pretreated nano-alumina copper. 7 parts of pretreated nano-alumina copper and 0.2 parts of 3-(methacryloyloxy)propyltrimethoxysilane were added to 50 parts of deionized water, homogenized at 700r / min for 30min, and then 2.5 parts of β-alanine methyl ester hydrochloride and 1 part of p-hydroxybenzamide were added, and homogenized at 700r / min for 30min to obtain a suspension. 2.5 parts of polyacrylic acid were added to 50 parts of deionized water and mixed evenly, and then the suspension was added dropwise at a speed of 2mL / min. After the addition was completed, stirring was continued for 1h, and after cooling to room temperature, centrifuged at 7000rpm for 5min, the precipitate was centrifuged at 7000rpm for 5min with anhydrous ethanol and deionized water, and the precipitate was vacuum dried at 80°C for 7h to obtain modified nano-alumina copper. 10 parts of modified nano-alumina copper were added into 100 parts of aqueous polyurethane emulsion, and stirred at 600 r / min for 1.5 hours to obtain a mixed emulsion.

[0035] Add 0.15 parts of 5040 dispersant, 0.2 parts of mono- and di-glycerol fatty acid esters and 6 parts of 4-toluene hydrogenamine resin to 50 parts of deionized water, homogenize at 800r / min for 30min, then add 1 part of ethyl p-hydroxyphenylacetate and 3 parts of vinyl MQ silicone resin, homogenize at 600r / min for 20min, then add 0.15 parts of 5040 dispersant and 0.2 parts of sodium dodecyl sulfate, homogenize at 600r / min for 20min, finally add the mixed emulsion, stir at 500r / min for 8h at 60℃ to obtain a modified emulsion. Take 5 parts of the modified emulsion and pour it into a mold with a size of 10×20mm and a thickness of 3mm, scrape the surface of the mold flat with a scraper, pre-cure at 35℃ for 5h, then cure at 80℃ for 13h, take it out after cooling, and obtain an aging-resistant thermal conductive polyurethane adhesive.

[0036] Example 4 10 parts of nano-alumina copper were added to 100 parts of anhydrous ethanol, ultrasonicated at 500r / min for 10 minutes, and then dried at 80°C for 3 hours to obtain pretreated nano-alumina copper. 6 parts of pretreated nano-alumina copper and 0.1 parts of 3-aminopropyltriethoxysilane were added to 50 parts of deionized water, homogenized at 600r / min for 20 minutes, and then 2 parts of β-alanine methyl ester hydrochloride and 1 part of p-hydroxybenzamide were added, and homogenized at 600r / min for 30 minutes to obtain a suspension. 4 parts of polyacrylic acid were added to 50 parts of deionized water and mixed evenly, and then the suspension was added dropwise at a speed of 2mL / min. After the addition was completed, stirring was continued for 1 hour. After cooling to room temperature, it was centrifuged at 7000rpm for 10 minutes, and the precipitate was centrifuged at 7000rpm for 8 minutes with anhydrous ethanol and deionized water, and the precipitate was vacuum dried at 80°C for 10 hours to obtain modified nano-alumina copper. 11 parts of modified nano-alumina copper were added into 100 parts of aqueous polyurethane emulsion, and stirred at 600 r / min for 1 hour to obtain a mixed emulsion.

[0037] Add 0.1 part of 5040 dispersant, 0.2 part of mono- and di-glycerol fatty acid esters and 5 parts of 4-toluene hydrogenamine resin to 50 parts of deionized water, homogenize at 700r / min for 20min, then add 1 part of ethyl p-hydroxyphenylacetate and 3 parts of vinyl MQ silicone resin, homogenize at 700r / min for 20min, then add 0.1 part of 5040 dispersant and 0.1 part of sodium dodecyl sulfate, homogenize at 600r / min for 20min, finally add the mixed emulsion, stir at 600r / min for 8h at 60℃ to obtain the modified emulsion. Take 5 parts of the modified emulsion and pour it into a mold with a size of 10×20mm and a thickness of 3mm, scrape the surface of the mold flat with a scraper, pre-cure at 25℃ for 4.5h, then cure at 70℃ for 15h, take it out after cooling, and obtain the aging-resistant thermal conductive polyurethane adhesive.

[0038] Example 5 10 parts of nano-alumina copper were added to 100 parts of anhydrous ethanol, ultrasonicated at 500r / min for 15min, and then dried at 80°C for 3.5h to obtain pretreated nano-alumina copper. 5 parts of pretreated nano-alumina copper and 0.1 parts of 3-aminopropyltriethoxysilane were added to 50 parts of deionized water, homogenized at 700r / min for 30min, and then 3 parts of β-alanine methyl ester hydrochloride and 2 parts of p-hydroxybenzamide were added, and homogenized at 700r / min for 20min to obtain a suspension. 3 parts of polyacrylic acid were added to 50 parts of deionized water and mixed evenly, and then the suspension was added dropwise at a speed of 2mL / min. After the addition was completed, stirring was continued for 1.5h, and after cooling to room temperature, it was centrifuged at 8000rpm for 10min, and the precipitate was centrifuged at 8000rpm for 10min with anhydrous ethanol and deionized water, and the precipitate was vacuum dried at 80°C for 7h to obtain modified nano-alumina copper. 8 parts of modified nano-alumina copper were added into 100 parts of aqueous polyurethane emulsion, and stirred at 700 r / min for 1.5 hours to obtain a mixed emulsion.

[0039] Add 0.2 parts of 5040 dispersant, 0.1 parts of mono- and di-glycerol fatty acid esters and 7 parts of 4-toluene hydrogenamine resin to 50 parts of deionized water, homogenize at 800r / min for 30min, then add 2 parts of ethyl p-hydroxyphenylacetate and 3 parts of vinyl MQ silicone resin, homogenize at 800r / min for 20min, then add 0.1 parts of 5040 dispersant and 0.2 parts of sodium dodecyl sulfate, homogenize at 800r / min for 20min, finally add the mixed emulsion, stir at 600r / min for 6h at 80℃ to obtain the modified emulsion. Take 5 parts of the modified emulsion and pour it into a mold with a size of 10×20mm and a thickness of 3mm, scrape the surface of the mold flat with a scraper, pre-cure at 25℃ for 4h, then cure at 75℃ for 13h, take it out after cooling, and obtain the aging-resistant thermal conductive polyurethane adhesive.

[0040] Example 6 10 parts of nano-alumina copper were added to 100 parts of anhydrous ethanol, ultrasonicated at 600r / min for 10 minutes, and then dried at 70°C for 3 hours to obtain pretreated nano-alumina copper. 6 parts of pretreated nano-alumina copper and 0.1 parts of 3-aminopropyltriethoxysilane were added to 50 parts of deionized water, homogenized at 700r / min for 30 minutes, and then 2.5 parts of β-alanine methyl ester hydrochloride and 1.5 parts of p-hydroxybenzamide were added, and homogenized at 600r / min for 30 minutes to obtain a suspension. 3 parts of polyacrylic acid were added to 50 parts of deionized water and mixed evenly, and then the suspension was added dropwise at a speed of 2mL / min. After the addition was completed, stirring was continued for 1.5 hours. After cooling to room temperature, it was centrifuged at 7000rpm for 10 minutes, and the precipitate was centrifuged at 8000rpm for 10 minutes with anhydrous ethanol and deionized water, and the precipitate was vacuum dried at 70°C for 8 hours to obtain modified nano-alumina copper. 12 parts of modified nano-alumina copper were added into 100 parts of aqueous polyurethane emulsion, and stirred at 700 r / min for 1.5 hours to obtain a mixed emulsion.

[0041] Add 0.15 parts of 5040 dispersant, 0.2 parts of mono- and di-glycerol fatty acid esters and 4 parts of 4-toluene hydrogenamine resin to 50 parts of deionized water, homogenize at 600r / min for 30min, then add 1 part of ethyl p-hydroxyphenylacetate and 3 parts of vinyl MQ silicone resin, homogenize at 600r / min for 20min, then add 0.15 parts of 5040 dispersant and 0.1 parts of sodium dodecyl sulfate, homogenize at 600r / min for 20min, finally add the mixed emulsion, stir at 600r / min for 7h at 70℃ to obtain a modified emulsion. Take 5 parts of the modified emulsion and pour it into a mold with a size of 10×20mm and a thickness of 3mm, scrape the surface of the mold flat with a scraper, pre-cure at 35℃ for 4h, then cure at 80℃ for 14h, take it out after cooling, and obtain an aging-resistant thermal conductive polyurethane adhesive.

[0042] The present invention also provides comparative examples and related tests.

[0043] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that, in the preparation process of the modified nano-alumina copper, 2 parts of p-hydroxybenzamide are not added, and the other compositions and preparation methods are the same as those of Example 1, and finally an aging-resistant thermally conductive polyurethane adhesive is prepared.

[0044] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that, in the process of preparing the modified nano-alumina copper, 1 part of β-alanine methyl ester hydrochloride is not added, and the other compositions and preparation methods are the same as those of Example 1, and finally an aging-resistant thermally conductive polyurethane adhesive is prepared.

[0045] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that modified nano-alumina copper is not prepared, and 10 parts of commercially available alumina are directly used to replace 10 parts of modified nano-alumina copper. The other compositions and preparation methods are the same as those in Example 1, and finally an aging-resistant thermally conductive polyurethane adhesive is prepared.

[0046] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that 5 parts of 4-toluene hydrogen amine resin are not added, and other compositions and preparation methods are the same as those of Example 1, and finally an aging-resistant thermally conductive polyurethane adhesive is prepared.

[0047] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that 1 part of ethyl p-hydroxyphenylacetate is not added, and the other compositions and preparation methods are the same as those of Example 1, and finally an aging-resistant thermally conductive polyurethane adhesive is prepared.

[0048] Performance testing The viscosity, tensile shear strength, shear impact strength and thermal conductivity of the aging-resistant thermally conductive polyurethane adhesives of Examples 1 to 6 and Comparative Examples 1 to 5 were tested according to the test methods described in GB / T2794-2022, GB / T33334-2016, GB / T6328-2021 and GB / T42919.1-2023, and the data were recorded as shown in Table 1.

[0049] Adhesion performance test: According to the provisions of GB / T2791-1995, the modified emulsions of Examples 1 to 6 and Comparative Examples 1 to 5 were used to prepare samples and perform peel strength tests, and the peel strength was used to express the test results. The data were recorded as shown in Table 1.

[0050] Aging resistance test: The aging resistance test of the aging-resistant thermal conductive polyurethane adhesives of Examples 1 to 6 and Comparative Examples 1 to 5 was carried out under artificial climate according to the tensile-compression cyclic durability test method for sealants under artificial climate aging in GB / T41753-2022, and the test results of the specimen surface were described according to the standard in GB / T41745-2022 and expressed as aging resistance. The data were recorded as shown in Table 1.

[0051] Water resistance test: The aging-resistant thermal conductive polyurethanes of Examples 1 to 6 and Comparative Examples 1 to 5 were bonded and cut into small cubes of 10×10 mm, and their mass was recorded as m0. They were then immersed in deionized water for 24 h. After being taken out, the moisture on the surface of the film was quickly absorbed with filter paper, and its mass was recorded as m1. The water absorption rate in water was calculated, and the water absorption rate = (m1-m0) / m0×100%. The data were recorded as shown in Table 1.

[0052] Table 1

[0053] It can be seen from the data in Table 1 that the aging-resistant thermally conductive polyurethane adhesives prepared in Examples 1 to 6 of the present invention have good aging resistance and thermal conductivity at room temperature. Among them, Example 1 has the best performance and is the best solution of the present invention.

[0054] According to the test results of water absorption, peel strength, aging resistance, thermal conductivity, viscosity, tensile shear strength, and shear impact strength of comparative examples 1 to 5 and embodiment 1, and combined with the data in Table 1, it can be seen that the water absorption of embodiment 1 is low and the aging resistance is good. The cracks after the aging resistance test can only be seen under a 10-fold magnifying glass, while comparative examples 3, 4, and 5 not only have high water absorption, but also have serious cracks, indicating that the water absorption and aging resistance of the adhesive prepared by replacing the modified nano-alumina copper with alumina and not adding 4-toluene hydrogenamine resin and ethyl p-hydroxyphenylacetate are poor. In addition, the thermal conductivity of comparative examples 1 and 2 is small, both below 1.5W / (m·K), indicating that the thermal conductivity of the prepared adhesive is weak when p-hydroxybenzamide and β-alanine methyl ester hydrochloride are not added.

[0055] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing an aging-resistant thermally conductive polyurethane adhesive, characterized in that: The following steps are involved: S1. After homogenizing the pretreated nano-alumina copper complex and silane in water, add β-alanine methyl ester hydrochloride and p-hydroxybenzamide to homogenize to obtain a suspension, add polyacrylic acid and the suspension to water in sequence, heat and stir, cool, centrifuge and dry to obtain a modified nano-alumina copper complex, and then add the mixture to an aqueous polyurethane emulsion and stir to obtain a mixed emulsion; S2, adding ethyl p-hydroxyphenylacetate to 4-toluene hydrogenamine resin and water to homogenize, and then adding the mixed emulsion to heat and stir to obtain a modified emulsion; S3, pouring the modified latex into a mold for curing to obtain an aging-resistant thermally conductive polyurethane adhesive.

2. The method for preparing an aging-resistant thermally conductive polyurethane adhesive according to claim 1, characterized in that: In the step S1, the nano-aluminum-copper is ultrasonically treated in ethanol at 500-600 r / min for 10-15 min, and then dried at 70-80° C. for 3-4 h to obtain the pretreated nano-aluminum-copper.

3. The method for preparing an aging-resistant thermally conductive polyurethane adhesive according to claim 1, characterized in that: In the step S1, the pretreated nano-alumina copper and silane coupling agent are homogenized in water, and then β-alanine methyl ester hydrochloride and p-hydroxybenzamide are added and homogenized to obtain a suspension.

4. The method for preparing an aging-resistant thermally conductive polyurethane adhesive according to claim 3, characterized in that: In the step S1, the homogenization speed is 600-800 r / min, and the homogenization time is 20-30 min; the silane coupling agent is any one of 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 3-(methacryloyloxy)propyltrimethoxysilane.

5. The method for preparing an aging-resistant thermally conductive polyurethane adhesive according to claim 1, characterized in that: In the step S1, polyacrylic acid is added to water and mixed evenly, and then the suspension is added dropwise at a speed of 2 mL / min, and stirring is continued for 1-2 hours after the addition is completed. After cooling to room temperature, the mixture is centrifuged at 7000-8000 rpm for 5-10 minutes, and the precipitate is centrifuged at 7000-8000 rpm for 5-10 minutes with ethanol and water respectively, and the precipitate is vacuum dried at 70-80° C. for 6-10 hours to obtain modified nano-alumina copper, which is then added to the aqueous polyurethane emulsion and stirred to obtain a mixed emulsion.

6. The method for preparing an aging-resistant thermally conductive polyurethane adhesive according to claim 5, characterized in that: In the step S1, the mixed emulsion is obtained by stirring the modified nano-alumina copper in the aqueous polyurethane emulsion at 600-800 r / min for 1-2 hours.

7. The method for preparing an aging-resistant thermally conductive polyurethane adhesive according to claim 1, characterized in that: In the step S2, the dispersant, mono- and di-glycerol fatty acid esters and 4-toluene hydrochloride resin are added to water for homogenization, then ethyl p-hydroxyphenylacetate and vinyl MQ silicone resin are added for homogenization, then the dispersant and sodium lauryl sulfate are added for homogenization, and finally the mixed emulsion is added for heating and stirring to obtain a modified emulsion.

8. The method for preparing an aging-resistant thermally conductive polyurethane adhesive according to claim 7, characterized in that: In the step S2, the homogenization speed is 600-800 r / min, and the time is 20-30 min; the dispersant is 5040 dispersant; the heating and stirring temperature is 60-80° C., the speed is 500-600 r / min, and the time is 6-8 h.

9. The method for preparing an aging-resistant thermally conductive polyurethane adhesive according to claim 1, characterized in that: In the step S3, the modified latex is poured into the mold, the surface of the mold is flattened with a scraper, pre-cured at 25-35° C. for 4-5 hours, and then cured at 70-80° C. for 12-15 hours to obtain an aging-resistant thermally conductive polyurethane adhesive.

10. An aging-resistant thermally conductive polyurethane adhesive, characterized in that: The adhesive is prepared by the method for preparing an aging-resistant thermally conductive polyurethane adhesive according to any one of claims 1 to 9, comprising the following raw materials in parts by weight: 10 parts of nano-alumina copper, 1 to 3 parts of β-alanine methyl ester hydrochloride, 1 to 2 parts of p-hydroxybenzamide, 2.5 to 5 parts of polyacrylic acid, 100 parts of aqueous polyurethane emulsion, 0.2 to 0.3 parts of 5040 dispersant, 0.1 to 0.2 parts of mono- and di-glycerol fatty acid esters, 1 to 2 parts of ethyl p-hydroxyphenylacetate, 4 to 7 parts of 4-toluene hydrogenamine resin, 3 to 4 parts of vinyl MQ silicone resin, and 0.1 to 0.2 parts of sodium dodecyl sulfate.

Citation Information

Patent Citations

  • Polyurethane adhesive for energy storage battery and preparation method of polyurethane adhesive

    CN117866579A